Offline study on loss optimization in distribution networks using Artificial Bee Colony (ABC) algorithm: article / Deezex Noor Ainizaa Abdullah - Abdullah, Deezex Noor Ainizaa (2009)
This paper present offline study on loss optimization in distribution networks using Artificial Bee Colony (ABC) algorithm. The study involves the development of Artificial Bee Colony (ABC) algorithm to implement loss minimization in a distribution system. Loss minimization can be achieved by performing network reconfiguration considering loss minimization as the objective function. The ABC algorithm was tested on the 14-bus radial distribution system and was programmed in Matlab 7.0. Results obtained from the experiments indicated that loss minimization has been successfully achieved.